Cytotoxic, Antiproliferative and Apoptosis‐inducing Activity of L‐Amino Acid Oxidase from Malaysian Calloselasma rhodostoma on Human Colon Cancer Cells. (25th July 2018) - Zainal Abidin, Syafiq Asnawi; Rajadurai, Pathmanathan; Chowdhury, Md. Ezharul Hoque; Ahmad Rusmili, Muhammad Rusdi; Othman, Iekhsan; Naidu, Rakesh
Abstract: The aim of this study was to investigate the cytotoxic, antiproliferative activity and the induction of apoptosis by L‐amino acid oxidase isolated from Calloselasma rhodostoma crude venom (CR‐LAAO) on human colon cancer cells. CR‐LAAO was purified using three chromatographic steps: molecular exclusion using G‐50 gel filtration resin, ion‐exchange by MonoQ column and desalted on a G25 column. The purity and identity of the isolated CR‐LAAO was confirmed by SDS‐PAGE and LC‐MS/MS. CR‐LAAO demonstrated time‐ and dose‐dependent cytotoxic activity on SW480 (primary human colon cancer cells) and SW620 (metastatic human colon cancer cells) with an EC50 values of 6 μg/ml and 7 μg/ml at 48 hr, respectively. Quantification of apoptotic cells based on morphological features demonstrated significant increase in apoptotic cell population in both SW480 and SW620 cells which peaked at 48 hr. Significant increase in caspase‐3 activity and reduction in Bcl‐2 levels were demonstrated following CR‐LAAO treatment. These data provide evidence on the potential anticancer activity of CR‐LAAO from the venom of C. rhodostoma for therapeutic intervention of human colon cancer.